Implementasi Pendidikan Agama Kristen Bagi Penguatan Keluarga Kristen Pada Era Industri 4.0 berdasarkan Matius 28:7, 10 di Jemaat GMIT Pniel Oebobo Kota Kupang - Harun Yermia Natonis (Institut Agama Kristen Negeri Kupang, 2023)
The purpose of this study is to describe Christian Religious Education for strengthening Christian families in the industrial era 4.0 based on Matthew 28:7, 10. This research uses a qualitative descriptive method. The data was traced and collected from various sources and literature such as religious leaders and congregations, then the researchers analyzed it by describing in a narrative manner the results of the research which suggested that Christian family life in the era of the industrial revolution 4.0 was important for members of the GMIT Pniel Oebobo family/congregation to have good awareness and understanding of the implications of technology, as well as practicing Christian values ??in everyday life. This involves developing self-discipline in using technology, prioritizing quality time with family, building healthy and meaningful relationships with others, and helping other family members to deal wisely with the impact of technology. The attitude of Christian families in dealing with the negative impacts of the industrial revolution 4.0 involves awareness, understanding and application of Christian values ??in the use of technology, church services, social empowerment, as well as cultural influences and social relations in the era of the industrial revolution 4.0.